Metabolism of carotenoid pigments and Vitamin A by swine - Parrish, D.B.; Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
Previous work has indicated• that vitamin A utilization and storage are reduced when pigs are infected with roundworms. Hygromix (S. hygroscopicus fermentation product, Lilly) has been used to reduce worm, infection in growing pigs. This test was to determine whether pigs with worm infection made less effective use of provitamin A from dehydrated alfalfa than did pigs in which worm infestation was reduced by feeding Hygromix.
Keywords: Swine; Carotenoid; Vitamin A